Aleviness, music, and hospitality - Bjelica, Maja (Muzikološki zbornik, 2022)
The paper examines urban Alevi traditional culture in Turkey as a possible example of an ethics of hospitality, drawing mainly from Alevi teachings and musical heritage. Through an examination of the lyrics of selected Alevi sacred songs the author presents various accounts of hospitality that are integral to Aleviness.
Keywords: Alevi music; aleviji; alevijska glasba; alevijstvo; Aleviness; deyiş; gostoljubje; hospitality; music; nefes